2010
DOI: 10.1016/j.socscimed.2009.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Stigma rises despite antiretroviral roll-out: A longitudinal analysis in South Africa

Abstract: a b s t r a c tStigma is a recognised problem for effective prevention, treatment, and care of HIV/AIDS. However, few studies have measured changes in the magnitude and character of stigma over time. This paper provides the first quantitative evaluation in Africa of the changing nature of stigma and the potential determinants of these changes. More specifically, it evaluates the dynamic relationship between stigma and (1) increased personal contact with people living with HIV/AIDS and (2) knowing people who di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
86
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 24 publications
7
86
1
Order By: Relevance
“…This is reflective of what is termed instrumental stigma. 59 Thus, the issue does not appear primarily to be prejudice; the issue appears to be a disproportionate fear of infection, and indeed, in our study, health care providers showed a kind of ambivalence. On the one hand, they wanted to provide good care to patients.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…This is reflective of what is termed instrumental stigma. 59 Thus, the issue does not appear primarily to be prejudice; the issue appears to be a disproportionate fear of infection, and indeed, in our study, health care providers showed a kind of ambivalence. On the one hand, they wanted to provide good care to patients.…”
Section: Discussionmentioning
confidence: 47%
“…58 In fact, most of the health care providers in our study did not express explicit negative attitudes about PLWH with accompanying moral judgments-something termed symbolic stigma. 59 Instead, most reported a fear of potential occupational infection resulting in the application of differential precautions and labeling of files. This is reflective of what is termed instrumental stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma, particularly HIV-related stigma, has been extremely resistant to interventions, including the impact of the roll-out of antiretrovirals and large public education programmes, with at least some evidence to suggest that stigma may be increasing in the Western Cape. 25 IPT is being distributed to those who are interested, but all three clinics identifi ed problems, particularly around staffi ng. As staff numbers are reduced, waiting times increase and staff unfamiliar with the patients may distribute the IPT, breaking down important interpersonal connections.…”
Section: Discussionmentioning
confidence: 99%
“…3 Living in a unique social environment, orphans with AIDS endure double pressure of disease and family and therefore are a vulnerable group. HIV-positive adolescent orphans mentioned in this article were born with HIV.…”
Section: Introductionmentioning
confidence: 99%